The role of fibroblast growth factor signalling in Echinococcus multilocularis development and host-parasite interaction. - Sabine Förster; Uriel Koziol; Tina Schäfer; Raphael Duvoisin; Katia Cailliau; Mathieu Vanderstraete; Colette Dissous; Klaus Brehm (Public Library of Science (PLoS), 2019)
BACKGROUND:Alveolar echinococcosis (AE) is a lethal zoonosis caused by the metacestode larva of the tapeworm Echinococcus multilocularis. The infection is characterized by tumour-like growth of the metacestode within the host liver, leading to extensive fibrosis and organ-failure. The molecular mechanisms of parasite organ tropism towards the liver and influences of liver cytokines and hormones on parasite development are little studied to date. METHODOLOGY/PRINCIPAL FINDINGS:We show that the E. multilocularis larval stage expresses three members of the fibroblast growth factor (FGF) receptor family with homology to human FGF receptors. Using the Xenopus expression system we demonstrate that all three Echinococcus FGF receptors are activated in response to human acidic and basic FGF, which are present in the liver. In all three cases, activation could be prevented by addition of the tyrosine kinase (TK) inhibitor BIBF 1120, which is used to treat human cancer. At physiological concentrations, acidic and basic FGF significantly stimulated the formation of metacestode vesicles from parasite stem cells in vitro and supported metacestode growth. Furthermore, the parasite's mitogen activated protein kinase signalling system was stimulated upon addition of human FGF. The survival of metacestode vesicles and parasite stem cells were drastically affected in vitro in the presence of BIBF 1120. CONCLUSIONS/SIGNIFICANCE:Our data indicate that mammalian FGF, which is present in the liver and upregulated during fibrosis, supports the establishment of the Echinococcus metacestode during AE by acting on an evolutionarily conserved parasite FGF signalling system. These data are valuable for understanding molecular mechanisms of organ tropism and host-parasite interaction in AE. Furthermore, our data indicate that the parasite's FGF signalling systems are promising targets for the development of novel drugs against AE.